Analisis Kemampuan Pasir Dari Pantai Nirwana Kota Padang Dan Pasir Dari Pantai Kawasan Mandeh Pesisir Selatan Sebagai Pengganti Pasir Ottawa Dalam Pengujian Sandcone: Analysis Of The Capability Of Sand From Nirwana Beach At Padang City And Sand From Mandeh Beach At Pesisir Selatan As Subtitutes For Ottawa Sand In Sandcone Testing - Prices, Afrizal Putra; Arlis, Angga Putra; Araska, Wahyu; Vernando, Vero Gusri; Husni, Alya Miftahul; Effendi, Effendi; Fitria, Winda; Afriyani, Sicilia (Media Ilmiah Teknik Sipil, 2025)
Ottawa sand has long been used as a standard material in geotechnical laboratory tests, particularly in grain size distribution and Sand Cone tests, due to its uniform particle size, purity, and stable physical properties. This study explores the potential of using beach sand from Nirwana and Mandeh as substitutes for Ottawa sand. The research process began with problem identification, followed by a literature review, sample collection, laboratory testing, and data analysis. The results show that the specific gravity of Nirwana sand (2.77) and Mandeh sand (2.72) are relatively close to Ottawa sand (±2.65). In terms of the coefficient of uniformity (Cu), Nirwana sand (2.34) is closer to Ottawa sand (2.17) compared to Mandeh sand (2.94). Regarding the coefficient of curvature (Cc), Nirwana sand (0.72) performs better than Mandeh sand (0.66), although both remain below the ideal range (1–3). Overall, Nirwana sand demonstrates greater potential as an alternative to Ottawa sand, with improvements in gradation recommended to achieve optimal performance.